Improving Critical Thinking Ability: Earthcomm Learning For Watershed Conservation Materials - Turohmahohmah, Fitri Dia Amana; Putra, Alfyananda Kurnia; Suharto, Yusuf (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Earth Science System in the Community is a learning model relevant to the 2013 curriculum and canimprove students' critical thinking ability. The research aims to determine the effect of EarthComm learningmodels assisted by Avenza Maps application on students critical thinking ability. This type of research is aquasi-experiment with a pretest-posttest control group design. The research was held at High School 2Mojokerto in the even semester 2019/2020. Data analysis using Independent Sample T-Test with IBM SPSSStatistics 22 for Windows. The results showed there was quite a significant difference between the criticalthinking ability of the experimental class and the control class, evidenced by the value gain a score of theexperiment class (28.11) more significant than the control class (19.89). EarthComm learning model assistedby Avenza Maps application affecting the students critical thinking ability because the syntax of EarthComminvites students to observe directly in the field. Through direct observation, students can feel and understandwhat is happening in the field to improve students' critical thinking ability. Suggestions are given to (1) theteacher of Geography subjects, hopefully, able to implement EarthComm learning model assisted by AvanzaMaps application about the Earth system material that demands critical thinking capabilities in it; (2) furtherresearchers, it is advisable to replace or add other bonded variables.